Orthoimages and digital surface models of the largest Argentine Islands in the Antarctic by UAV photogrammetry - Lamsters, Kristaps; Karušs, Jānis; Krievāns, Māris; Ješkins, Jurijs (Zenodo, 2019)
These data contain photogrammetrical data collected by unmanned aerial vehicle (UAV) from February to March 2018 in the Argentine Islands, Wilhelm Archipelago, West Antarctica. The data include processed data (orthoimages and digital surface models) with the Structure-fom-Motion photogrammetrical software Agisoft Metashape. Data are cropped by the outlines of islands. Data are organized by the name of the surveyed island. The coordinate system used is UTM Zone 20S based on WGS84. The data are related to the article "High-resolution orthophoto map and digital surface models of the largest Argentine Islands (the Antarctic) from unmanned aerial vehicle photogrammetry", Lamsters, K., Karušs, J., Krievāns, M., Ješkins, J., 2020. Journal of Maps. https://doi.org/10.1080/17445647.2020.1748130 : This work was financially supported by the specific support objective activity 1.1.1.2. "Post-doctoral Research Aid" (Project id. N. 1.1.1.2/16/I/001) of the Republic of Latvia, funded by the European Regional Development Fund, Kristaps Lamsters research Project No. 1.1.1.2/VIAA/1/16/118.